Mangrove species act as potential biofilters for legacy organochlorine pesticides: evidence from tissue-specific accumulation in the Zhangjiang Estuary - Nemin Luo; Ting Fang; Yingying Qian; Lei Wang; Wenhui Lin; Rongrong Song; Guoxin Li; Fengrun Wu; Xiaoqing Chen; Mingyuan Lin; Yan Lin (Marine Environmental Research, 2026)

PLGA nanoparticles encapsulating fibroblast growth factor 21 alleviate acetaminophen-induced acute liver injury - Jie Lin; Guoxin Jin; Ling Zhang; Xiu Weng; Kecheng Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Decoding the molecular network communication mechanism of ketamine’s antidepressant effects - Ye Li; Qilong Cheng; Guoxin Lin; Kaiming Duan; Saiying Wang (Psychopharmacology, 2026)

Far-UVC-driven Cr(VI) reduction in alkaline solution: Synergistic effects of iodide and sulfite - Yida Huang; Min Zhao; Guoxin Li; Yan Lin; Lei Wang (Journal of Environmental Sciences, 2026)

Genome Wide Identification, Expression Profiles and Regulatory Network Analysis of SOS Group of Genes in Camellia Sinensis - Surjit Bhattacharjee; Abhirup Paul; Aradhana Jana; Deepak R; G. Meher Unnati; Wang Li; Archita Chatterjee; Chen Lin; Guoxin Shen; Neelam Mishra (Tropical Plant Biology, 2025)

Predicting joint loading in Asian overweight and obese females with flexible flatfoot: a regression analysis of anthropometric parameters and gait dynamics - Linjuan Wei; Guoxin Zhang; Tony Lin-Wei Chen; Yan Wang; Yinghu Peng; Ming Zhang (Medical & Biological Engineering & Computing, 2025)
Current methods for obtaining accurate joint loading data lack simplicity, efficiency, and cost-effectiveness. This study aims to generate joint loading prediction models using anthropometric parameters and walking speed in overweight or obese females with flexible flatfoot. Sixteen participants’ motion capture data from walking trails and anthropometric parameters were collected. The lower limb joint contact forces and the walking speed were calculated via a musculoskeletal model. Regression analysis was used to generate the prediction model. The second peak of knee joint contact force revealed a strong negative correlation with hip circumference and a weak positive correlation with age ( p < 0.001 and adjusted R 2 = 0.720). The peak ankle joint contact force exhibited a strong positive correlation with walking speed while strong negative correlations with waist circumference and lower limb length ( p < 0.001 and adjusted R 2 = 0.782). The first peak of vertical GRF displayed a medium negative correlation with walking speed ( p < 0.001 and adjusted R 2 = 0.750). Anthropometric parameters and walking speed are effective predictors of joint loading. This rapid, low-cost estimation method can be applied to areas such as flexible flatfoot that require assessment of joint stress, thereby saving costs and time. Graphical abstract

In-Situ Encapsulation of AIEgens in Nanoconfined Pores Over MOFs for High-Resolution Recognition of 3-Level Latent Fingerprint - Liqin Lu; Yan Wang; Ziheng Huang; Liang Meng; Fenglan Li; Guosong Lin; Zhechong Zheng; Guoxin Zhuang (Journal of Fluorescence, 2025)

Multi-target-responsive AIE material for in situ visualization of level 3 features in latent fingerprints - Guoxin Zhuang; Jinxin Wei; Yonglin Wen; Yujing Li; Youpeng Xu; Yisheng Jiang; Xianghui Lai; Liang Meng; Zhiyu Liang; Xiaohui Lin; Lijun Ma; Guosong Lin; et al. (Analytica Chimica Acta, 2025)

Priming effects by cellulose inputs decrease with warming regardless of the decomposition stages of soil carbon pools - Junjie Lin; Guoxin Lan; Zhenyu Yang; Shuang Zhou; Dafeng Hui; Peng Wang; Shuai Zhang; Lifeng Ping; Shengdao Shan (Plant and Soil, 2025)

Thermal sensitivity and rising greenhouse gas emissions in riparian zone soils: Implications for ecosystem carbon dynamics - Shuxun Cheng; Amit Kumar; Guoxin Lan; Wenling Zhang; Zhuolin Yu; Shuai Zhang; Zhi-Guo Yu; Meijuan Yao; Junjie Lin (Journal of Environmental Management, 2025)

Effect of microplastics on carbon, nitrogen and phosphorus cycle in farmland soil: A meta-analysis - Guoxin Lan; Xiaohang Huang; Tongqing Li; Yingjie Huang; Yang Liao; Qiushi Zheng; Qin Zhao; Yue Yu; Junjie Lin (Environmental Pollution, 2025)

Soft yet powerful: Nano-coatings preserve transfer film integrity - Xiaoyi Wu; Xin Han; Lin Zhang; Mengyu Li; Guoxin Xie (Chemical Engineering Journal, 2025)

Synthesis of cholesterol analogues and comparison on their effect on plasma cholesterol with β-Sitosterol - Hanyue Zhu; Longjian Chen; Zi-Xing Chen; Huiqi Lin; Jianhui Liu; Erika Kwek; Ka Ying Ma; Wensen He; Guoxin Wang; Zhen-Yu Chen (Food Chemistry, 2024)

Textural properties prediction of KOH-activated carbon prepared from coal based on pyrolysis kinetics - Kai Wang; Guoxin Lin; Jun Meng; Jiangmin Guo; Bo Tan; Shaojun Liu; Qingyang Lin; Xuecheng Wu; Xiang Gao (Waste Disposal & Sustainable Energy, 2024)

Degradation induced superlubricity on the rough surface of black phosphorus composite - Yi Zhang; Jianguo Jiao; Hao Chen; Kai Gao; Yilong Ren; Yunze Li; Lin Zhang; Guoxin Xie; Jianbin Luo (Chemical Engineering Journal, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

The variability in CYP3A4 activity determines the metabolic kinetic characteristics of ketamine - Mengfang Li; Qingqing Li; Dan Lin; Xiang Zheng; Lehao Jin; Jianping Cai; Guoxin Hu; Jianchang Qian (Toxicology, 2023)

Ultralow friction polymer composites enabled by the solid–liquid core microcapsules at high temperatures - Hao Chen; Yi Zhang; Kai Gao; Yilong Ren; Jianguo Jiao; Lin Zhang; Dan Guo; Guoxin Xie (Chemical Engineering Journal, 2023)

Engineering conductive and catalytic triple-phase interfaces for high efficiency polysulfides conversion in Li-S batteries - Benben Wei; Yang Tu; Yu Xia; Wolfgang Theis; Junxian Zhang; Zian Xu; Shaoqing Chen; Jian Chen; Guoxin Yin; Hsing-Lin Wang (Chemical Engineering Journal, 2023)

Ultrabright orange-yellow aggregation-induced emission nanoparticles for highly sensitive immunochromatographic quantification of ochratoxin A in corn - Guoxin Chen; Xirui Chen; Ge Xu; Xiaxia Wei; Xiangkai Lin; Yu Su; Yonghua Xiong; Xiaolin Huang (Food Chemistry, 2023)

Advantages of aggregation-induced luminescence microspheres compared with fluorescent microspheres in immunochromatography assay with sandwich format - Xiaxia Wei; Xirui Chen; Zilong Liu; Ge Xu; Guoxin Chen; Xiangkai Lin; Wenchao Zhan; Xiaolin Huang; Yonghua Xiong (Analytica Chimica Acta, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

Exosomes from patients with Parkinson’s disease are pathological in mice - Chao Han; Nian Xiong; Xingfang Guo; Jinsha Huang; Kai Ma; Ling Liu; Yun Xia; Yan Shen; Jie Li; Haiyang Jiang; Luxi Wang; Shiyi Guo; et al. (Journal of Molecular Medicine, 2019)

Fenpropathrin, a Widely Used Pesticide, Causes Dopaminergic Degeneration - Jing Xiong; Xiaowei Zhang; Jinsha Huang; Chunnuan Chen; Zhenzhen Chen; Ling Liu; Guoxin Zhang; Jiaolong Yang; Zhentao Zhang; Zhaohui Zhang; Zhicheng Lin; Nian Xiong; et al. (Molecular Neurobiology, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Lead-induced oxidative damage in steriled seedlings of Nymphoides peltatum - Xuqiang Qiao; Guoxin Shi; Lin Chen; Xiuli Tian; Xiaoying Xu (Environmental Science and Pollution Research, 2013)